Science Education beyond Constructivism - Jain, H.C. (Educational Trend (A Journal of RIE, Ajmer - NCERT), 2020)
Constructivism in the last few decades has acquired the status of a grand theory to impart meaningful learning. However, further researches indicate that constructivism does not provide a flawless epistemology; there is difference between how scientific knowledge is created and how it is learnt. Keeping these points in view, a critical appraisal of constructivist approach has been given in this paper. It suggests realistic pedagogy beyond constructivism to be used to study different entities encountered in the world. Further, other approaches viz. Navigationism and Allosteric Model have also been discussed. It is concluded that there is no unique method which can be considered as wholly effective for teaching and learning but the approach has to be manifold.